Percutaneous Transluminal Angioplasty Balloon‐Assisted Adjacent Vascular Connection Without Stent Protection: Case Report - Xiaoyi Sun; Xiang Shao; Weixin Kong; Hejing Liu; Xiang Li (Clinical Case Reports)
ABSTRACT The aneurysmal dilation and excessive blood flow of the cephalic vein caused by the relative stenosis of the cephalic venous arch are important challenges in the maintenance of arteriovenous fistulas, and the use of adjacent vascular connection without stent protection has shown great advantages over traditional open surgery.